Residential area deprivation and risk of subsequent hospital admission in a British population: the EPIC-Norfolk cohort. Issue 12 (16th December 2019) - Luben, Robert; Hayat, Shabina; Khawaja, Anthony; Wareham, Nicholas; Pharoah, Paul P; Khaw, Kay-Tee
Abstract : Objectives: To investigate whether residential area deprivation index predicts subsequent admissions to hospital and time spent in hospital independently of individual social class and lifestyle factors. Design: Prospective population-based study. Setting: The European Prospective Investigation into Cancer in Norfolk (EPIC-Norfolk) study. Participants: 11 214 men and 13 763 women in the general population, aged 40–79 years at recruitment (1993–1997), alive in 1999. Main outcome measure: Total admissions to hospital and time spent in hospital during a 19-year time period (1999–2018). Results: Compared to those with residential Townsend Area Deprivation Index lower than the average for England and Wales, those with a higher than average deprivation index had a higher likelihood of spending >20 days in hospital multivariable adjusted OR 1.18 (95% CI 1.07 to 1.29) and having 7 or more admissions OR 1.11 (95% CI 1.02 to 1.22) after adjustment for age, sex, smoking status, education, social class and body mass index. Occupational social class and educational attainment modified the association between area deprivation and hospitalisation; those with manual social class and lower education level were at greater risk of hospitalisation when living in an area with higher deprivation index (p-interaction=0.025 and 0.020, respectively), while the risk for non-manual and more highly educated participants did not vary greatly by area of residence. Conclusion: Residential area deprivation predicts future hospitalisations, time spent in hospital and number of admissions, independently of individual social class and education level and other behavioural factors. There are significant interactions such that residential area deprivation has greater impact in those with low education level or manual social class. Conversely, higher education level and social class mitigated the association of area deprivation with hospital usage.